A laser based straightness monitor for a prototype automated linear collider tunnel surveying system - Moss, G (2013)
For precise measurement of new TeV-scale physics and precision studies of the Higgs Boson, a new lepton collider is required. To enable meaningful analysis, a centre of mass energy of 500GeV and luminosity of 1034cm-2s-1 is needed. The planned 31km long International Linear Collider is capable of meeting these targets, requiring a final emittance of 10 micro-radians horizontally and 35nmrad vertically. To achieve these demanding emittance values, the accelerator components in the main linacs must be aligned against an accurately mapped network of reference markers along the entire tunnel. An automated system could map this tunnel network quickly, accurately, safely and repeatedly; the Linear Collider Alignment and Survey (LiCAS) Rapid Tunnel Reference Surveyor (RTRS) is a working prototype of such a system. The LiCAS RTRS is a train of measurement units that accurately locate regularly spaced retro-reflector markers using Frequency Scanning Interferometry (FSI). The unit locations with respect to each other are precisely reconstructed using a Laser Straightness Monitor (LSM) and tilt sensor system, along with a system of internal FSI lines. The design, commissioning, practical usage, calibration, and reconstruction performance of the LSM is addressed in this work. The commissioned RTRS is described and the properties of the LSM components are investigated in detail. A method of finding the position of laser beam spots on the LSM cameras is developed, along with a process of combining individual spot positions into a more robust measurement compatible with the data from other sub-systems. Laser beam propagation along the LSM is modelled and a robust method of reconstructing CCD beam spot position measurements into positions and orientations of the LSM units is described. A method of calibrating LSM units using an external witness system is presented, along with a way of using the overdetermined nature of the LSM to improve calibration constant errors by including data taken from unwitnessed runs. The reconstruction uncertainty, inclusive of both statistical and systematic effects, of the LSM system is found to be of 5.8 microns × 5.3 microns in lateral translations and 27.6 microradians × 34.1 microradians in rotations perpendicular to the beam, with an uncertainty of 51.1 microradians in rotations around the beam coming from a tilt-sensor arrangement.